Evolving radon diffusion through earthen barriers at uranium waste disposal sites. (June 2023) - Fuhrmann, Mark; Caldwell, Todd G.; Likos, William J.; Waugh, W.J.; Williams, Morgan M.; Benson, Craig H.
Abstract: Field measurements of Rn-222 fluxes from the tops and bottoms of compacted clay radon barriers were used to calculate effective Rn diffusion coefficients (DRn ) at four uranium waste disposal sites in the western United States to assess cover performance after more than 20 years of service. Values of DRn ranged from 7.4 × 10 −7 to 6.0 × 10 −9  m 2 /s, averaging 1.42 × 10 −7 . Water saturation (SW ) from soil cores indicated that there was relatively little control of DRn by SW, especially at higher moisture levels, in contrast to estimates from most steady-state diffusion models. This is attributed to preferential pathways intrinsic to construction of the barriers or to natural process that have developed over time including desiccation cracks, root channels, and insect burrows in the engineered earthen barriers. A modification to some models in which fast and slow pathway DRn values are partitioned appears to give a good representation of the data; 4% of the fast pathway was needed to fit the data regression. For locations with high Sw and highest DRn (and fluxes) at each site, the proportion of fast pathway ranged from 1.7% to 34%, but for many locations with lower fluxes, little if any fast pathway was needed. Highlights: Rn diffusion coefficients (DRn ) were determined at 4 uranium waste disposal sites. Little control of DRn by water saturation (SW ) especially at higher moisture levels. Field results after 20+ years of service are different than original design models. DRn with fast and slow pathway values is result of soil structure development. A simple approach to evaluating fast pathways is provided.